Radar techniques using array antennas - Wirth, Wulf-Dieter (IET radar, sonar, navigation and avionics series, 2001)
This book gives an introduction to the possibilities of radar technology based on active array antennas, giving examples of modern practical systems, many of which were developed in Europe. In addition to coverage of antennas, array signal processing, adaptive digital beamforming, adaptive monopulse, superresolution, and sequential detection, several modern systems are described including space-time adaptive processing (STAP), moving target detection using synthetic aperture radar (SAR), and several other experimental phased array radar systems. There are many valuable lessons presented for de.